2020
DOI: 10.1111/cea.13803
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of early‐onset rhinitis in the Singapore GUSTO mother‐offspring cohort

Abstract: Background The natural history of childhood rhinitis is not well described. Objective This study aimed to identify different rhinitis trajectories in early childhood and their predictors and allergic associations. Methods Rhinitis symptoms were ascertained prospectively from birth until 6 years using standardized questionnaires in 772 participants. Rhinitis was defined as one or more episodes of sneezing, runny and/or blocked nose >2 weeks duration. Latent trajectories were identified using group‐based modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The effect of maternal PUFAs might also be outweighed by other environmental factors which are more relevant to allergy development in our cohort, such as smoking exposure and childcare center attendance during infancy. 6 We observed that higher maternal total n-3:total n-6 PUFAs and (DHA + EPA):AA ratios were associated with a higher risk of early life wheeze by 18 months, especially in non-atopic children.…”
mentioning
confidence: 65%
“…The effect of maternal PUFAs might also be outweighed by other environmental factors which are more relevant to allergy development in our cohort, such as smoking exposure and childcare center attendance during infancy. 6 We observed that higher maternal total n-3:total n-6 PUFAs and (DHA + EPA):AA ratios were associated with a higher risk of early life wheeze by 18 months, especially in non-atopic children.…”
mentioning
confidence: 65%
“…In this context, it can be assumed that social status might be a proxy measure for behavioral patterns 27 . Loo et al 28 also found that higher maternal education was a risk factor for allergic rhinitis. These results agree with a systematic review of 183 studies showing a higher prevalence of rhinitis in higher socioeconomic status groups 29 .…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, the use of the ISAAC does not allow for the diagnosis of rhinitis, but for the reporting of symptoms. However, most epidemiological studies have been performed in school-age children using the ISAAC questionnaire 28 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent cohort studies suggest that childhood AR is heterogenous in its development. 6,7 Although classical hypothesis stated that AR is a risk factor for asthma in atopic march, 7 complete manifestation of the march was found only in a small population. 6 Precise process of the onset of AR in children is still to be studied because most of the epidemiological studies relied on questionnaire in the absence of definitive diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…to 13–14 y.o 5 . Recent cohort studies suggest that childhood AR is heterogenous in its development 6,7 . Although classical hypothesis stated that AR is a risk factor for asthma in atopic march, 7 complete manifestation of the march was found only in a small population 6 …”
Section: Introductionmentioning
confidence: 99%